Institutional culture and internationalisation: a study of Black African academics' experiences at Rhodes University - Wambua, Lloyd M (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
This research sets out to examine institutional culture and internationalisation in higher education in contemporary South Africa, by analysing the experiences of black foreign academics at Rhodes University. Much has been written on the adaptation processes of foreign students in South African universities (Ayliff and Wang, 2006; Dzansi and Monnapula-Mapesela, 2012; Mudhovozi, 2011). There is also a host of literature on the black South African experience of adaptation and (non) belonging at historically white universities (HWU) (Akoojee and Nkomo, 2007; Cornell and Kessi, 2017; Soudien, 2008). Comparatively less is written on whether there are any unique pressures regarding institutional culture that black foreign African academics face at historically white institutions such as Rhodes University. The black experience may be misrepresented as a homogenous one by much of the literature on higher education transformation (Batsai, 2019). But there are a host of factors that could change your experience of being 'black', such as your class, and gender and quite recently there has been a push to further examine the effect that one's nationality has on their experience of being 'black' in the academy (Batsai, 2019). Institutional culture refers to the "behaviours and values that make up the unique psychological and social environment of a certain institution" (Toma et al., 2005). Internationalisation of higher education in the context of Africa, particularly South Africa refers to "the intentional or unintentional process to integrate intercultural, international and global dimensions in higher education" (Draft Policy Framework for the Internationalisation of Higher Education in South Africa, 2017). In analysing the experiences of international African academics, this research is trying to give a voice to an often-overlooked group of individuals. This research is also meant to portray the black experience in South African higher education as an experience that is not homogenous but reliant on a host of unique identity factors such as gender, class and also their nationality.
Keywords: Corporate culture -- South Africa -- Makhanda; Universities and colleges -- South Africa -- Makhanda -- Sociological aspects; Discrimination in higher education -- South Africa -- Makhanda; Rhodes University; College teachers, Black -- South Africa -- Makhanda -- Social conditions; College teachers, Foreign -- South Africa -- Makhanda -- Social conditions; Globalization -- South Africa -- Makhanda; Educational change -- South Africa -- Makhanda; Sex discrimination in higher education -- South Africa -- Makhanda; South Africa -- Race relations; Intersectionality (Sociology); Pan-Africanism; Belonging (Social psychology); Alienation (Social psychology)